2022
DOI: 10.1007/978-3-030-97322-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Induced Migration in West Africa

Abstract: Although West Africa’s contribution to global climate change is very minimal, its geographical location and weak adaptive capacity makes it highly vulnerable to the effects of climate change and variability. The livelihoods of people in the dry regions of West Africa, in particular, are adversely affected by increased temperature and fluctuating rainfall patterns because they depend on rain-fed agriculture and ecosystem services. Flooding is also a common climate-induced hazard in some West African countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the DHS household survey, the migration history of household members is not available, making it challenging to thoroughly examine possible biases related to displacement. However, previous studies have indicated that, unlike slow-onset climate change, which often results in permanent and widespread displacement, disasters often trigger large but short-term displacement, typically to nearby regions, followed by relatively rapid return (33)(34)(35). The small-scale of permanent displacements from affected areas following sudden-onset disasters, such as tropical cyclones in our case, should make this bias small.…”
Section: Discussionmentioning
confidence: 59%
“…In the DHS household survey, the migration history of household members is not available, making it challenging to thoroughly examine possible biases related to displacement. However, previous studies have indicated that, unlike slow-onset climate change, which often results in permanent and widespread displacement, disasters often trigger large but short-term displacement, typically to nearby regions, followed by relatively rapid return (33)(34)(35). The small-scale of permanent displacements from affected areas following sudden-onset disasters, such as tropical cyclones in our case, should make this bias small.…”
Section: Discussionmentioning
confidence: 59%
“…The increasing frequency and severity of climate-related disasters such as floods and droughts can lead to more permanent migration over time. Urbanization can bring about migratory movements from the countryside to the cities [18].…”
Section: Introductionmentioning
confidence: 99%